A novel chrome-free tanning approach based on sulfonated tetraphenyl Calix[4]resorcinarene: Preparation and application. (10th November 2018) - Zhou, Yongxiang; Ma, Jianzhong; Gao, Dangge; Li, Wenbo; Shi, Jiabo; Ren, Huijun
Abstract: Chrome tannage is the main tanning method because of its excellent hydrothermal stability and physical performances. However, the chromium absorption is limited, so the emissions of solid wastes can bring many environmental issues and human health risks. Therefore, a novel chrome-free tanning agent based on a water-soluble calixarene has been attempted. Water-soluble calixarene is a chemical with a unique molecular structure, thermal stability and high chemical stability, it contains a lot of more active coordination of phenolic hydroxyl. In this work, tetraphenyl calix [4]resorcinarene (TC4R) was synthesized with one-step process, and then was sulfonated by concentrated sulfuric acid, which obtained the sulfonated tetraphenyl calix [4]resorcinarene (STC4R). The chemical structure of the TC4R and STC4R were detected by IR and H-NMR. Then STC4R was added to the tanning process as an experimental process and 6% conventional chrome tannage was added to tanning as control. The result shows that the Ts of tanned leather is 77.2 °C using 10% STC4R at final pH 4.0. SEM analyses show that collagen fibers have been dispersed, STC4R makes the fiber loosen and the fullness is increased. FT-IR shows that the hydrogen bond is formed between phenol hydroxyl of sulfonated calixarenes and amino of collagen in the tanning process. At the same time, STC4R does not enter the micro fibrils within the collagen, so three helix structures are not damaged and consistent with AFM.